Agricultural systems research and global food security in the 21st century: An overview and roadmap for future opportunities. (June 2018) - Stephens, Emma C.; Jones, Andrew D.; Parsons, David
Abstract: This article presents a brief history and overview of some key intersections between agricultural systems research and the literature on global food security. It also serves to contextualize the submissions for this special issue, which comprise selected relevant research presented at the 2nd International Conference on Global Food Security, held at Cornell University in October 2015. Highlights: Overview of intersections between agricultural systems and food security research Summaries of new research bridging agricultural systems and food security questions Identification of future research needs between and across these two domains